ALTERNATING SSFP PERMITS RAPID, BANDING-ARTIFACT-FREE BALANCED SSFP FMRI - Patterson, Steve (2013)
Blood oxygenation level dependent (BOLD) functional magnetic resonance imaging (fMRI) is the dominant tool used for mapping human brain function because it is non-invasive, does not use ionizing radiation, and offers relatively high spatial and temporal resolution compared to other neuroimaging techniques. Unfortunately, conventional fMRI techniques cannot map brain function in the inferior temporal cortex (ITC) and orbitofrontal cortex (OFC). These brain regions experience severe magnetic field distortions due to magnetic susceptibility mismatch with the neighboring air-filled ear-canals (ITC) or sinus cavities (OFC), causing loss of the fMRI signal. Functional imaging capability is important for gaining a better understanding of these brain regions and the diseases that commonly affect them (Alzheimer’s disease and epilepsy (ITC), Parkinson’s disease and schizophrenia (OFC)). Balanced steady state free precession (balanced SSFP) is a relatively new fMRI technique that can measure function in all brain regions. Rather than diffuse signal loss, balanced SSFP images exhibit signal loss in spatially periodic, narrow bands. Banding artifacts cannot be eliminated in a single scan, but the phase of the banding artifacts can be controlled by the experimenter, permitting the combination of two antiphase balanced SSFP images to produce a single image free of banding artifacts. Unfortunately, image-corrupting transient signal oscillations limit the rate at which the banding artifact phase can be modified, such that the banding-artifact-free image acquisition rate is prohibitively slow for most clinical and neuroscience applications. This work describes the development of a modified balanced SSFP fMRI technique, alternating SSFP, which permits rapid, banding-artifact-free balanced SSFP fMRI. Theoretical modeling was used to find a rapid transition between antiphase balanced SSFP images with minimal transient signal oscillations. Monte Carlo simulations were used to optimize alternating SSFP acquisition parameters for BOLD sensitivity, with comparison to established balanced SSFP acquisitions. Rat fMRI was used to confirm these predictions. Finally, the ability of alternating SSFP to provide rapid, banding-artifact-free balanced SSFP fMRI in humans at 4 T was demonstrated.